Magnetic and magnetoresistive characteristics of neutron-irradiated Si₀.₉₇Ge₀.₀₃ whiskers - Litovchenko, P.G.; Pavlovska, N.T.; Pavlovskyy, Yu.V.; Ugrin, Yu.O.; Luka, G.; Ostrovskyy, I.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
The effect of 8.6∙10¹⁷ n/cm² with fast neutron irradiation on the magnetic susceptibility of Si₀.₉₇Ge₀.₀₃ thread-like crystals (whiskers) with impurity concentration near metal-insulator junction has been studied. Significant differences have been observed in the change of magnetic susceptibility of irradiated whiskers and bulk Cz-Si. The low-temperature (4.2…40 K) changes of magnetoresistance in magnetic fields up to 14 T, caused by irradiation, have been studied. It has been established that at temperatures near 4.2 K, a significant contribution to the conductivity is made by light charge carriers of low concentration but with high mobility. The level supplying these charge carriers has the energy of e = 2.1 meV, and with application of magnetic field it increases up to e = 2.5 meV in approx. 10 T field. It demonstrates the fact that the reason of magnetoresistance, beside the magneto-field decrease of mobility, is the magneto-field decrease in the free carrier concentration. At temperatures approx. 40 K, conductivity is due to holes, the activation energy whereof is e = 11.5 meV, which is practically independent of the magnetic field.